2012
DOI: 10.1051/0004-6361/201118578
|View full text |Cite
|
Sign up to set email alerts
|

Deprojected analysis of Abell 1835 observed withChandraand compared withXMM-Newton

Abstract: Using a deprojection technique, we study the X-ray properties of the galaxy cluster Abell 1835 observed with Chandra, including temperature, abundance, electron density, gas mass fraction, and total mass. A comparison with the results without deprojection shows that the properties do not change much. When we compare the results with those of XMM-Newton, the difference between the temperature profiles derived from Chandra and XMM-Newton data still exists, even if the point-spread function effect of XMM-Newton i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Figure 1 shows the fit to the projected temperature profile (blue line) assuming a deviation of the entropy from the profile k ∼ r a at r > r b ; this because a powerlaw increase is inconsistent with the Chandra data (see the green line). From the surface brightness distribution (see Figure 1), we derive the ICP density profile of Figure 2 in a slightly different way than the deprojected electron density profile obtained by Li et al (2012) from Chandra observations and in agreement with the profile derived at r 180 by the Suzaku observations (Ichikawa et al 2013). As shown in Figure 5, the gas density profile gives a central SZ effect value absolutely consistent with the observations (Reese et al 2002), at variance with the gas density profile derived by Li et al (2012).…”
Section: Supermodel Analysis Of A1835supporting
confidence: 72%
See 2 more Smart Citations
“…Figure 1 shows the fit to the projected temperature profile (blue line) assuming a deviation of the entropy from the profile k ∼ r a at r > r b ; this because a powerlaw increase is inconsistent with the Chandra data (see the green line). From the surface brightness distribution (see Figure 1), we derive the ICP density profile of Figure 2 in a slightly different way than the deprojected electron density profile obtained by Li et al (2012) from Chandra observations and in agreement with the profile derived at r 180 by the Suzaku observations (Ichikawa et al 2013). As shown in Figure 5, the gas density profile gives a central SZ effect value absolutely consistent with the observations (Reese et al 2002), at variance with the gas density profile derived by Li et al (2012).…”
Section: Supermodel Analysis Of A1835supporting
confidence: 72%
“…From the surface brightness distribution (see Figure 1), we derive the ICP density profile of Figure 2 in a slightly different way than the deprojected electron density profile obtained by Li et al (2012) from Chandra observations and in agreement with the profile derived at r 180 by the Suzaku observations (Ichikawa et al 2013). As shown in Figure 5, the gas density profile gives a central SZ effect value absolutely consistent with the observations (Reese et al 2002), at variance with the gas density profile derived by Li et al (2012). Moreover, our SZ effect profile reproduces fairly well the profile observed by Bolocam at r 30 (Sayers et al 2011).…”
Section: Supermodel Analysis Of A1835mentioning
confidence: 97%
See 1 more Smart Citation
“…The Chandra data are performed by CIAO 4.3 and CALDB 4.4.0. We analyze the Chandra data following the method discussed in Li et al (2012). The tool LC CLEAN in CIAO is used to scan the light curve of data for flares, and the Good Time Intervals (GTIs) are selected.…”
Section: Sample Selection and Data Analysismentioning
confidence: 99%
“…By multiplying the effective area of Chandra/ACIS with the corresponding splines of the stacked residuals, Schellenberger et al (2014) changed the energy dependence of effective area and found that the temperatures between Chandra/ACIS and XMM-Newton/pn were consistent. Li et al (2012) tried to fit Chandra spectra with XMM-Newton temperatures and presented that the modified Chandra mass of Abell 1835 was consistent with the XMM-Newton mass. These works focused on looking for the reasons of discrepancy in temperature or mass, but they didn't give an correction relation which can be used directly in combining Chandra and XMM-Newton data to build a large sample.…”
Section: Introductionmentioning
confidence: 99%